A exploração industrial sustentável do patrimônio genético - Boverio, Paulo Henrique Fernandes (2021)
The genetic heritage has become more and more, with the advancement of science, the target of multiple scientific researches in view of the rich potential of industrial exploration of this unique asset that makes up a national biodiversity. Thus, the interest of the industry grows, with regard to the most varied segments, to finance the production and commercialization of the result of the chemical composition of information of genetic origin from living beings of all species, whether animal, vegetable, microbial or fungal. In these terms, it is important to mention that the genetic heritage, although inserted in the concept of environmental good of a transindividual nature, enjoying wide protection of the legal system, is not an intangible revelation. This is because, experiments focused on actions in genetic heritage and associated knowledge can legitimately be the target of industrial exploration. Even because it is an important industrial activity sector, capable of generating wealth and strengthening the national economy. What must be observed are the constitutional imperatives, in addition to the multiple international treaties to which Brazil is a signatory, in which the concern to protect the environment for future generations is evident, so that industrial exploitation is sustainable, that is, or, respecting the current order, especially the deontic modes that are characterized as interpretive vectors, that is, the environmental principles created and developed by the laws, doctrine and jurisprudence over the years.